A dynamic simplified Lund model for large-eddy simulation and its application to a centrifugal pump. Issue 7 (15th October 2018) - Huang, Xianbei; Qiu, Baoyun; Guo, Qiang; Liu, Zhuqing; Yang, Wei; Li, Yaojun
Abstract : Purpose: Construct a new sub-grid scale (SGS) model which can improve the efficiency and maintain comparative accuracy comparing to the existing dynamic cubic non-linear SGS model (DCNM). Design/methodology/approach: The polynomial constitutive relation between the SGS stress tensor and both strain and rotation rate is selected as a basement. Simplification is achieved by eliminating the solid-body rotation term and adopting the assumption proposed by Kosovic. A dynamic procedure is applied to calculate three model coefficients in the new model. The new model (named dynamic simplified Lund model) and DCNM are applied to the rotating channel flow and the internal flow in a centrifugal pump impeller to examine the performance. Findings: The new model is as accurate as DCNM but decreases 25 per cent computational resources. The ability of capturing rotation effect and reflecting backscatter is verified through cases. In addition, good numerical stability is shown during the calculation. Research limitations/implications: More benchmark and engineering cases should be used to get further confidence on the new model. Practical implications: The new model is promising in industrial application with the advantage of both accuracy and efficiency. For the flow with large-scale separation or more complicate phenomenon, the model is thought to give accurate flow structure. Originality/value: A new non-linear SGS model is proposed in this paper. The accuracy, numerical stability and efficiency are validated for this model. Therefore, it is promising in the prediction of the flow structure in centrifugal pumps.